(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the geopolitical position and situation of Central Asia. It examines the regional characteristics of Central Asia, its place in today’s global geopolitical processes and system of interests, its geopolitical opportunities and complexities, as well as the main factors shaping the geopolitical interests of powerful states and global power centers in the region.